Crack Propagation Simulation and Meshing Stiffness Analysis of Disposable Harmonic Gears - Zhang Yuxin; Pan Xudong; Li Yuefeng; Wang Guanglin; Zhang Qingyu (Jixie chuandong)
The mechanical equipment in aerospace field that will not be reused after being used once is called disposable machinery. The failure of the flexible wheel is the most important factor affecting the performance of the disposable harmonic reducer. The change of the meshing stiffness can reflect the fault characteristics of the harmonic drive. In this study, the disposable and conventional harmonic gears are distinguished from the application environment and structure. Then, the crack initiation position of the flexible wheel in the disposable harmonic drive is analyzed. Besides, the damage model of the disposable harmonic flexible has been established based on the extended finite element method, and the crack propagation path of the flexible wheel rim is observed. Finally, the effect of cracks on the meshing stiffness of the disposable harmonic drive is discussed. The research conclusions of this study can provide theoretical support for fault diagnosis and life prediction of disposable harmonic gears.